AN ANALYSIS OF THE EXPRESSIVE SPEECH ACTS IN “THE WILLOUGHBYS” MOVIE - Aritonang, Roby Octo; Ambalegin, Ambalegin (BASIS (Bahasa dan Sastra Inggris), 2023)
This research focuses on identifying the expressive speech acts found in “The Willoughbys” Movie. The research uses the theory of Searle and Vanderveken (1985). The method is observation in collecting the data, and the technique is note-taking. In analyzing the data, the data was examined with the pragmatic identity method and pragmatic competence-in-equalizing technique. The data was taken from the utterances in the movie. There are 67 expressive speech acts found in the movie which are divided into 11 acts. The expressive speech acts with the most occurrences were complaints with 12 occurrences, followed by 6 data of greet, 4 data of apologies, 6 data of compliments, 10 data of protest, 9 data of lament, 3 data of thanks, 3 data of boast, 5 data of praise, 4 data of condole, and 5 data of deplore. The expressive speech acts of congratulate was not found in the movie, because the scene mostly was found in their journey and their adventure that they had to do.